Monetary policy spillover to small open economies: Is the transmission different under low interest rates? - Cao, Jin; Dinger, Valeriya; Gómez, Tomás; Gric, Zuzana; Hodula, Martin; Jara, Alejandro; Juelsrud, Ragnar; Liaudinskas, Karolis; Malovaná, Simona; Terajima, Yaz (Journal of Financial Stability, 2023)
We explore the impact of low and negative monetary policy rates in core world economies on bank lending in four small open economies – Canada, Chile, the Czech Republic and Norway – using confidential bank-level data. We show that the impact on lending in these small open economies depends on the interest rate level in the core. During normal times, monetary policy cuts in the core can reduce credit supply in small open economies. In contrast, when interest rates in the core are low, further expansionary monetary policy increases lending in small open economies, consistent with an international bank lending channel. These results have important policy implications, suggesting that central banks in small open economies should watch for the impact of potential regime switches in core economies’ monetary policy when rates shift to and from the very low end of the distribution.